2009
DOI: 10.1021/ie801294n
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Separation of Noble Gases by IRMOF-1: Grand Canonical Monte Carlo Simulations

Abstract: The gas storage capacity of metal-organic frameworks (MOFs) is well-known and has been investigated using both experimental and computational methods. Previous Monte Carlo computer simulations of gas adsorption by MOFs have made several questionable approximations regarding framework-framework and framework-adsorbate interactions: potential parameters from general force fields have been used, and framework atoms were fixed at their crystallographic coordinates (rigid framework). We assess the validity of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
126
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(138 citation statements)
references
References 84 publications
10
126
1
1
Order By: Relevance
“…It is notable that with a diameter less than 2 nm, no condensations are occurred because the system becomes onedimensional 56 , as for SW-CN-Ts. Those explanations are proved with the experimental result for Neon adsorption 57 and molecular simulation results for Helium, Xenon and Argon mixture 59 .…”
Section: Resultssupporting
confidence: 60%
“…It is notable that with a diameter less than 2 nm, no condensations are occurred because the system becomes onedimensional 56 , as for SW-CN-Ts. Those explanations are proved with the experimental result for Neon adsorption 57 and molecular simulation results for Helium, Xenon and Argon mixture 59 .…”
Section: Resultssupporting
confidence: 60%
“…As demonstrated in a recent simulation study on the adsorption of noble gases in IRMOF-1, rigid and semi-flexible frameworks gave close results at both low and room temperatures. [40] The LJ interactions were evaluated with a spherical cut off of 13 with the longrange corrections added; the Coulombic interactions were calculated using the Ewald sum. The real/reciprocal space partition parameter and the cut off for reciprocal lattice vectors were chosen to be 0.2 À1 and 8, respectively, to ensure the convergence of the Ewald sum.…”
Section: à2mentioning
confidence: 99%
“…Recently, the research team reported that a MOF known as Ni/DOBDC has a Xe capacity of 4.16 mol/kg at 1 bar and 298 K, which is higher than that of a charcoal carbon . Greathouse et al (2009) used grand canonical Monte Carlo (GCMC) simulation to investigate Xe and Kr separation in a MOF known as IRMOF-1. Ryan and Snurr et al (2011) simulated Xe and Kr separation with several other MOFs with GCMC.…”
Section: Tablesmentioning
confidence: 99%